Contracts, Biases, and Consumption of Access Services - Leider, Stephen; Şahin, Özge (Management Science, 2014)
We study theoretically and empirically the consumption of access services. We demonstrate that consumption is affected by contract structure (pay-per-use versus three-part tariffs) even if the optimal consumption plans are identical. We find that, although there is extensive individual heterogeneity, on average, consumers' choices follow a structure that is similar to a nearly optimal heuristic and correctly react to imbalances between the number of free calls and call opportunities remaining. However, consumers use the free units too quickly, leading to overconsumption and lost surplus. These errors are partially driven by mistaken beliefs about the value distribution. We also measure subjects' willingness to pay for a contract with free access units, and we find that nearly half of subjects are willing to pay at least the full per-unit price, with a substantial fraction willing to overpay. In response, the optimal firm strategy offers a three-part tariff at a very small discount, which increases revenue by 8%–14% compared to only offering a pay-per-use contract. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2013.1889 . This paper was accepted by Teck-Hua Ho, behavioral economics.